Comparison of curved canal preparations by means of three different root canal curvature measurement techniques - (:unkn) unknown (My University, 2019)
Aim: The aim of this study was to compare the effects of twodifferent rotary systems on the original canal curvature by meansof three different root canal curvature measurement techniques.Materials and Method: Mesiobuccal canals of thirty extractedhuman mandibular first and second molar teeth wereequally allocated into two groups: Mtwo or ProTaper. Afterembedding in clear acrylic resin, preoperative radiographswere taken. Both systems were used according to the manufacturers’instructions. Pre- and postoperative angular andlinear values of mesiobuccal canals were obtained from radiographsusing AutoCAD R12.Results: In both groups, the postoperative canal access angle(CAA) and Schneider angle (SA) were significantly decreased(p≤ 0.005). Postoperative AC distance (the distance betweencanal entrance and the point that the canal begins to moveaway from the long axis) significantly increased only in theProTaper group (p=0.005).Conclusion: The lack of a change in the AC distance in theMtwo group indicated that the original canal curvature wasmaintained. Postoperative AC distance should also be measured,besides CAA and SA, in order to evaluate changes inthe root canal curvature after root canal preparation.

Amaç: Bu çalışmanın amacı iki farklı döner eğe sisteminin, orijinal kök kanal eğimi üzerindeki etkilerinin üç farklı kök kanal eğimi ölçüm tekniği ile karşılaştırılarak incelenmesidir. Gereç ve Yöntem: Otuz adet çekilmiş alt çene birinci ve ikinci büyük azı dişinin meziyobukkal kanalları Mtwo veya ProTaper ile şekillendirilmek üzere eşit olarak iki gruba ayrılmıştır. Dişler şeffaf akrilik rezin içine gömüldükten sonra pre-operatif radyografileri çekilmiştir. Her iki döner eğe sisteminin eğeleri üretici firma talimatları doğrultusunda kullanılmıştır. Meziyobukkal kanalların başlangıç ve işlem sonrası açısal ve doğrusal değerleri AutoCAD R12 programı kullanılarak radyografiler üzerinden hesaplanmıştır. Bulgular: Her iki grupta da genişletme sonrası kanal giriş açıları (CAA) ve Scheider açıları (SA) anlamlı derecede azalmıştır (p≤ 0.005). Genişletme sonrası AC uzunluğu (kanal girişi ile kanalın uzun aksından ayrılmaya başladığı nokta arası mesafe) sadece ProTaper gurubunda belirgin olarak artmıştır (p=0.005). Sonuç: Mtwo grubunda AC uzunluğunda değişiklik olmaması kanalın orjinal eğimini koruduğunu göstermektedir. Kök kanal şekillendirilmesi sonrası kanal eğimlerindeki değişikliklerin ölçülmesinde CAA ve SA açılarının yanısıra işlem sonrası AC uzunluğu da ölçülmelidir.
Eğri kanalların şekillendirilmesinin üç farklı kök kanal eğimi ölçüm yöntemi ile karşılaştırılması
Keywords: Diş Hekimliği